Renal Infarcts—A Perplexing Case in the Middle of the COVID-19 Pandemic - Plouffe, Brett; Van Hooren, Tamara; Barton, Michelle; Nashid, Nancy; Demirkaya, Erkan; Norozi, Kambiz; Rachinsky, Irina; Delport, Johan; Knauer, Michael; Tole, Soumitra; Filler, Guido (Frontiers in Pediatrics, 2021)
Renal infarction is a rare finding in children. Associations between SARS-CoV-2 infections and thromboembolic events including renal infarcts have been described in adults. Although a similar association in children has not yet been described with this pandemic, the pediatric literature is still evolving with the recognition of new manifestations including the post-infectious Multisystem Inflammatory Syndrome in Children (MIS-C). We report the rare event of multiple renal infarcts in a 6-year-old boy manifesting several features of MIS-C 9 weeks following a self-limiting febrile illness characteristic of COVID-19. An underlying Factor V Leiden mutation was identified in this child but felt to be insufficient on its own to explain his clinical presentation. As SARS-CoV-2 testing was delayed, the failure to identify viral RNA or antibodies may not exclude the virus’ potential role in precipitating the infarct in this host. Given that renal infarcts have been described in adult patients with COVID-19, reporting this perplexing case where SARS-CoV-2 may have played a role, may help identify this potential complication.